Impact of Tooth Loss and Preferences for Tooth Replacement Among Clinic Attendees at a Public University - Fang, Hew Pei; En, Lee Jia; Meei, Tew In; Ahmad, Rohana; Abdul Aziz, Aznida Firzah; Said, Shahida Mohd; Mohd Dom, Tuti Ningseh (Journal of Dentistry Indonesia, 2018)
Tooth loss is considered a major end-point sequela of preventable oral diseases. In Malaysia, tooth mortality is a common oral health problem. Objective: To assess the impact of tooth loss, preferences for tooth replacement, and the relationship between impact of tooth loss and number of missing teeth. Methods: This descriptive cross-sectional survey involved 244 patients attending a primary health center and dental clinic at a public university. The respondents completed self-administered questionnaires on personal background, tooth replacement status, impact of tooth loss using a 12-item modified Geriatric Oral Health Assessment Index (GOHAI), and preferences for tooth replacement. A dental examination was performed to determine the number of missing teeth. Results: The mean age of the respondents was 56.2 years (standard deviation [SD], 8.1 years). The mean number of missing teeth was 8.3; 62.7% of patients had at least 20 natural teeth. The majority were not wearing a dental prosthesis. The mean GOHAI score was 16.3. Of the patients, 66.0% experienced some food biting difficulty, 59.4% worried about oral health, and 57.8% experienced eating discomfort. Dental implants were the most preferred replacement option (38.9%). The GOHAI scores were not related to the number of missing teeth. Conclusion: Tooth loss and use of dental prostheses had some impact on quality of life, although the impact was not high.